Trends in patient visits before and during the COVID-19 pandemic: a case in a public health center - Kusumastiwi, Pipiet Okti; Raharja, Giras Budi; Damayanti, Sella Shaquila; Azzahra, Nisriina Yusan Nindy (BKM Public Health and Community Medicine, 2025)
Purpose: This study examines changes in patient visits before and during the COVID-19 pandemic in a public health center. Methods: Employing longitudinal descriptive research, data were extracted from the clinic's register book using purposive sampling at the Dental Polyclinic Tepus II at the Public Health Center in Gunung Kidul, Yogyakarta. The study focused on patients receiving scaling, tooth extraction, and filling treatments, comparing data from ten months before and during the pandemic. Results: The analysis reveals a noticeable reduction in patient numbers during the pandemic, particularly for scaling treatments. Despite the decline, the clinic continued to offer dental services, with consistent visits for tooth extractions. Gender distribution and JKN payment methods remained unchanged. The most significant drop in patient visits occurred in the second month of the pandemic, with a gradual recovery to pre-pandemic levels by the 9th and 10th months. Conclusion: The COVID-19 pandemic decreased patient visits, with the most affected service being scaling. Despite these challenges, the clinic upheld its commitment to providing essential dental care, adapting to the new normal, and recovering patient volumes to pre-pandemic figures.